Eco-Architecture IV 2012
DOI: 10.2495/arc120271
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable strategies and methods for the energetic improvement of social housing stock in Italy

Abstract: This paper seeks to investigate the use of sustainable strategies of intervention in the refurbishment of social suburban building stock considering some public buildings in Emilia Romagna region of ACER (Emilia Romagna housing company) ownership. In this study, interventions on the envelope and the installations, in order to improve architectural and energetic performance following the new European Energy Standards for energy savings, have been considered. Besides the technology and architectural result, an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The study shows a mapping that analysed the building performance and concluded that the PMCMV basic singlefamily floorplan provides poor outcomes, especially in hot climates. Passive and bioclimatic architecture (Brunoro, 2012;Colclough;Kinnane;Hewitt;Griffiths, 2018;Muñoz Cruz et al, 2017;Preciado-Pérez;Fotios, 2017;Rincón;Carrobé;Martorell;Medrano, 2019;Suárez;Fernández-Agüera, 2015) has been presented in the literature as an essential factor to improve affordable housing performance. Among the strategies, optimising the solar orientation of dwellings is expected to improve their thermal performance and energy efficiency levels (Bodach;Hamhaber, 2010;Franco et al, 2019;Taleb;Yeretzian;Jabr;Hajj, 2020;Sassi, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The study shows a mapping that analysed the building performance and concluded that the PMCMV basic singlefamily floorplan provides poor outcomes, especially in hot climates. Passive and bioclimatic architecture (Brunoro, 2012;Colclough;Kinnane;Hewitt;Griffiths, 2018;Muñoz Cruz et al, 2017;Preciado-Pérez;Fotios, 2017;Rincón;Carrobé;Martorell;Medrano, 2019;Suárez;Fernández-Agüera, 2015) has been presented in the literature as an essential factor to improve affordable housing performance. Among the strategies, optimising the solar orientation of dwellings is expected to improve their thermal performance and energy efficiency levels (Bodach;Hamhaber, 2010;Franco et al, 2019;Taleb;Yeretzian;Jabr;Hajj, 2020;Sassi, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The application of ETICS became in the last ten years a popular measure to improve the energy performance and the weather resistance of façades in the building stock. Even if it is frequently supposed that the small thickness of the exterior plaster and a smooth insulation material as substrate are possible causes for damage from mechanical impact, many experiences can demonstrate that the costs and frequency of maintenance for ETICS are less than those of traditional wall structures [2,5]. Energy regulation standards in Emilia Romagna region for walls is expressed with a maximum thermal transmittance (U value) of 0.34 W/m 2 K. In the most cases, initial wall transmittance was higher that 1.2 W/m 2 K: this means that 12 cm of extruded polystyrene insulation layer was considered (Fig.…”
Section: External Thermal Insulation Coatingmentioning
confidence: 99%